2009
DOI: 10.1097/nmd.0b013e3181925342
|View full text |Cite
|
Sign up to set email alerts
|

Early Adverse Experiences in Schizophrenia and Unipolar Depression

Abstract: To study the prevalence of early adversities in schizophrenia and unipolar depression, 2 groups of consecutive adult-onset inpatients with DSM-IV diagnoses of schizophrenia (n = 173) and unipolar depression (n = 305) were compared with an unscreened control group of volunteers from the general population (n = 310), with respect to their association with 4 types of childhood abuse and with early parental adversities (discord, separation, death, psychiatric caseness). Compared with general population, most types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
46
1
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 23 publications
5
46
1
2
Order By: Relevance
“…Although the studies assessed in this systematic review showed controversial evidence regarding the subtype of early life stress associated with anxiety disorders and mood disorders, Holowka, King, Saheb, Pukall, and Brunet (2003) and Rubino, Nanni, Pozzi, and Siracusano (2009) demonstrated consistent findings about the important role of emotional abuse in the etiology of schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…Although the studies assessed in this systematic review showed controversial evidence regarding the subtype of early life stress associated with anxiety disorders and mood disorders, Holowka, King, Saheb, Pukall, and Brunet (2003) and Rubino, Nanni, Pozzi, and Siracusano (2009) demonstrated consistent findings about the important role of emotional abuse in the etiology of schizophrenia.…”
Section: Resultsmentioning
confidence: 99%
“…This may vary with the 'dose' or intensity of experience, with different amounts of adversity cumulatively increasing the risk or predicting the onset of severe disorders (Rubino et al, 2009;Sugaya et al, 2012;Mueser et al, 2002). It may also vary with the definition of severe disorder: while increasing amounts of various adversities increase the risk in different disorders Read and Bentall, 2010), no dose effect was found for first-presentation psychosis patients (Fisher et al, 2010;Sideli et al, 2012).…”
Section: Introductionmentioning
confidence: 84%
“…Comparisons of diagnostic groups and type of maltreatment show more or less specific associations: focusing on the study of one diagnostic group may suggest a specific impact, for example, of early sexual abuse and BPD (e.g., Wingenfeld et al, 2010) or punishment and psychosis (Fisher et al, 2010), while comparisons of types of adversities and diagnostic groups suggest less specificity Rubino et al, 2009;Matheson et al, 2012;Anda et al, 2002;McLaughlin et al, 2010a,b). This may vary with the 'dose' or intensity of experience, with different amounts of adversity cumulatively increasing the risk or predicting the onset of severe disorders (Rubino et al, 2009;Sugaya et al, 2012;Mueser et al, 2002).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Abuse, neglect, and separation from either one or both parents during childhood have been shown to be associated with a greater risk of mental health disorders (Afifi et al, 2006(Afifi et al, , 2009Danese et al, 2009;Green et al, 2010;Hjern et al, 2002;Johnson et al, 1999Johnson et al, , 2006M€ akikyr€ o et al, 1998;Morgan et al, 2007;Pesonen et al, 2007;Rubino et al, 2009;Rusby and Tasker, 2009;Sharon et al, 2009;Thompson et al, 2008;Tieman et al, 2005;Veijola et al, 2004Veijola et al, , 2008Widom, 1999;Widom et al, 2007Widom et al, , 2009. Also parental separation during childhood has been shown to have detrimental psychological long-term consequences (Birtchnell and Kennard, 1984;Breier et al, 1988;Foster et al, 2003;Kendler et al, 1992Kendler et al, , 2002Pesonen et al, 2007;Tennant et al, 1982).…”
mentioning
confidence: 95%